Why is Cognitive Enhancement Deemed Unacceptable? The Role of Fairness, Deservingness, and Hollow Achievements - Faber, Nadira S.; Savulescu, Julian; Douglas, Thomas (Frontiers in Psychology, 2016)
We ask why pharmacological cognitive enhancement (PCE) is generally deemed morally unacceptable by lay people. Our approach to this question has two core elements. First, we employ an interdisciplinary perspective, using philosophical rationales as base for generating psychological models. Second, by testing these models we investigate how different normative judgements on PCE are related to each other. Based on an analysis of the relevant philosophical literature, we derive two psychological models that can potentially explain the judgement that PCE is unacceptable: the “Unfairness-Undeservingness Model” and the “Hollowness-Undeservingness Model”. The Unfairness-Undeservingness Model holds that people judge PCE to be unacceptable because they take it to produce unfairness and to undermine the degree to which PCE-users deserve rewards. The Hollowness-Undeservingness Model assumes that people judge PCE to be unacceptable because they find achievements realized while using PCE hollow and undeserved. We empirically test both models against each other using a regression-based approach. When trying to predict judgements regarding the unacceptability of PCE using judgments regarding unfairness, hollowness, and undeservingness, we found that unfairness judgments were the only significant predictor of the perceived unacceptability of PCE, explaining about 36% of variance. As neither hollowness nor undeservingness had explanatory power above and beyond unfairness, the Unfairness-Undeservingness Model proved superior to the Hollowness-Undeservingness Model. This finding also has implications for the Unfairness-Undeservingness Model itself: either a more parsimonious single-factor “Fairness Model” should replace the Unfairness-Undeservingness-Model or fairness fully mediates the relationship between undeservingness and unacceptability. Both explanations imply that participants deemed PCE unacceptable because they judged it to be unfair. We conclude that concerns about unfairness play a crucial role in the subjective unacceptability of PCE and discuss the implications of our approach for the further investigation of the psychology of PCE.